Teach like your hair's on fire : the methods and madness inside room 56 - Esquith, Rafe. (New York : Viking, 2007)
In a Los Angeles neighborhood plagued by guns, gangs, and drugs, there is a classroom known as Room 56. The fifth graders inside are first-generation immigrants who live in poverty and speak English as a second language. They also play Vivaldi, perform Shakespeare, score in the top 1% on standardized tests, and go on to attend Ivy League universities. Rafe Esquith is the teacher responsible for these accomplishments. Here, he reveals his techniques. The classroom's mottoes are "Be nice, work hard," and "There are no shortcuts."
Keywords: Education -- Philosophy; Ethics -- Study and teaching; Moral education; Values -- Study and teaching